Analysis of the Influence of Work Environment and Communication on Employee Performance of PT. Citas Otis Elevator Medan - Hendri Rusly; Yessica Sardina Purba (Jurnal Mantik, 2022)
This study aims to determine the effect of environment and communication on employee performance of PT. Citas Otis Elevator Medan. This type of research is explanatory research. The population in this study were all employees of PT. Citas Otis Elevator totaling 61 employees. The sampling technique is to use a saturated sample where the entire population will be used as the research sample. In the study which will be distributed with questionnaires measured by a Likert scale. The data analysis used multiple linear regression analysis and the coefficient of determination as well as simultaneous test and partial test. The results showed that environment and communication partially or simultaneously have a positive and significant effect on employee performance of PT. Citas Otis Elevator Medan. Based on the results of this study, the implications for management are to further improve environment and communication.